Screening of wild okra against okra leafhopper insect, Amarasca biguttula biguttula - SINGH, S P; KUMARI, POOJA; GANGOPADHYAY, K K; DUBEY, S C (The Indian Journal of Agricultural Sciences, 2021)
A total 76 germplasm accessions of wild okra (Abelmoschus moschatus ssp. moschatus) along with 4 checks were evaluated against okra leafhopper Amarasca biguttula biguttula Ishida in field condition during kharif 2017 and 2019. Of the 76 wild okra accessions used for two years of field screening, negligible preference of okra leafhopper insect exhibited towards nine wild okra accessions namely EC360586, EC360794, EC360830, EC360900, EC359730, EC359836, EC359870, EC360351 and EC361171 with hopper population in the range of 1.33 to 1.44/leaf while moderate preference of okra leafhopper was observed to another 11 wild okra accessions during first year of field screening (kharif 2017). During the second year (kharif 2019) of field screening, negligible preference of okra leafhopper was recorded on five accessions, viz. EC360586, EC360794, EC360830, EC360900 and EC361171 with hopper population in the range of 1.33 to 1.45/leaf while moderate preference response of okra leafhopper was observed on two wild okra accessions only. Whereas, high to very high preference response of okra leafhopper was observed on the remaining wild okra accessions during both the years of field screening and all were found susceptible. Based on two years field screening of wild okra accessions against okra leafhopper, five wild okra accessions, viz. EC360586, EC360794, EC360830, EC360900 and EC361171 were found resistant against okra leafhopper. The hopper burn symptoms were also negligible on these 5 accessions.